2015
DOI: 10.3354/esr00683
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic right whale occurrence near wind energy areas along the mid-Atlantic US coast: implications for management

Abstract: The distribution and seasonal patterns of the North Atlantic right whale, Eubalaena glacialis, inform management decisions that mitigate anthropogenic threats. Based on data from visual surveys, much of the population migrates between winter calving grounds in coastal waters adjacent to the southeast USA and summer feeding and nursery grounds adjacent to the northeast USA. However, little is known about right whale occurrence along the mid-Atlantic US migratory corridor. A better understanding of right whale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…In this study, concurrent acoustic monitoring by the Cornell University Lab of Ornithology revealed a longer period of occurrence than the shorter seasonal period that was detected by aerial surveys . Re cent studies of E. glacialis distribution in coastal areas that used a combination of acoustic and visual assessment techniques found that aerial surveys were useful for estimating abundance and identifying individuals, but that acoustic monitoring detected occurrence over longer periods of time (Whitt et al 2013, Hodge et al 2015, Oedekoven et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, concurrent acoustic monitoring by the Cornell University Lab of Ornithology revealed a longer period of occurrence than the shorter seasonal period that was detected by aerial surveys . Re cent studies of E. glacialis distribution in coastal areas that used a combination of acoustic and visual assessment techniques found that aerial surveys were useful for estimating abundance and identifying individuals, but that acoustic monitoring detected occurrence over longer periods of time (Whitt et al 2013, Hodge et al 2015, Oedekoven et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Potential up‐calls that were repeated at regular intervals or that were closely associated with other frequency‐modulated sounds likely to be from humpbacks were considered to be humpbacks or of ambiguous species identity and were eliminated. This conservative approach to discriminating between right whale up‐calls and humpback sounds is similar to that used in other studies (Hodge et al, ; Mellinger et al, ; Mussoline et al, ; Salisbury et al, ). Detected sounds within each hour were examined only until one confirmed up‐call was found.…”
Section: Methodsmentioning
confidence: 94%
“…This is the first study to quantify interannual variation in right whale year‐round use of a specific area over more than 3.5 years. Earlier PAM studies have provided important insights into right whale presence at places or times of year where they had previously not been observed in modern times (Bort et al, ; Hodge et al, ; Mellinger et al, ; Morano et al, ; Mussoline et al, ; Salisbury et al, ; Whitt et al, ). However, with the exception of the study by Morano et al (; see below), which used a subset of the data reported here, those studies were limited to 1 or (in one case: Whitt et al, ) 2 years at any given site, providing useful but limited snapshots of habitat use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Hodge et al . ), putative up‐calls in the presence of additional frequency‐modulated sounds reoccurring often within 3–5 s were discarded as most likely being a humpback whale, whereas individual up‐calls with longer intercall intervals were considered to be from right whales. We estimated that contact calls could be detected on the MARUs at a range of approximately 10–20 km (Clark et al .…”
Section: Methodsmentioning
confidence: 99%